2016
DOI: 10.3991/ijep.v6i3.5765
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Curriculum to Enhance the Learning Experience of Electrical and Mechanical Engineering Students

Abstract: Abstract-This paper presents an integrated engineering enrichment program for the electrical and mechanical engineering students at polytechnic level. This program promotes design thinking and problem based learning and it is spread into three years of engineering education. The entire program is founded upon design-and-build type of projects where students get to practice engineering design process with increasing complexity in each semester. It is implemented in a studio environment equipped with necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…The dual features of the learning objectives are contrasted with the contextual approach, which implies the choice of the educational content with a higher degree of the necessary material for the implementation of a given type of activity. The structure of the course is developed based on the type of activity [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…The dual features of the learning objectives are contrasted with the contextual approach, which implies the choice of the educational content with a higher degree of the necessary material for the implementation of a given type of activity. The structure of the course is developed based on the type of activity [17,31].…”
Section: Discussionmentioning
confidence: 99%
“…Ercan, Sale and Kristian observed that "certain key features such as interdisciplinary, collaborative active and experiential learning, and authentic assessment for learning" develop the "engineering as well as communication and teamwork skills of students […] significantly". [11] The scope of subjects introducing making activities is wide, even using a makerspace for ocean technology education [27] was investigated. Another study found "that students who use the space either for class projects or for their own personal projects had significantly higher inmajor GPAs than students who did not use the space" [10].…”
Section: Maker Culture Interdisciplinary and Opennessmentioning
confidence: 99%
“…PBL is part of many teaching activities for electrical engineering. This integration includes single courses [4], [5], enrichment programs [6] as well as complete curricula [7].…”
Section: Challenges and Conceptmentioning
confidence: 99%
“…Depending on the size, the complexity and the components the development is split into several smaller projects, e.g. development of the electric power steering for the E-Kart [6]. These initial developments are done either by students performing their bachelor or master thesis or by student teams in terms of PBL.…”
Section: Concept Of Rolling Labsmentioning
confidence: 99%
See 1 more Smart Citation